Investigating the Effect of Deactivation Rate Constant of Polymer-Based Silver Catalyst on the Reduction of Pollutant 4-Nitrophenol to 4-Aminophenol - Navid Ahadi-Jomairan; Ali Nematollahzadeh; Behruz Mirzayi (مجله مدل سازی در مهندسی)
The catalytic reduction of the organic pollutant, 4-nitrophenol to 4-aminophenol was simulated as a model reaction in contact with the polymer-based silver catalyst in a packed bed. The decrease in the catalyst activity as a result of the product residues on the catalyst and also the effect of the deactivation rate constant and conversion rate changes was investigated. Three different values for the deactivation rate constant were chosen as 4.8´10-5, 2.4´10-4, and 1.2´10-3 m3 mol-1 s-1. The results showed that by increasing the catalyst deactivation rate constant, at the end of the studied time, the conversion decreases by 2, 10, and 70%, respectively, and the catalyst activity decreases by 25, 75, and 95%, respectively. Also, the activity of the catalyst throughout the catalytic bed exhibited a greater drop compared to the upper part of the bed due to the accumulation of the product in the lower part of the bed. Therefore, it is important to choose an appropriate catalyst with the minimum deactivation rate constant to achieve the highest conversion percentage and the highest catalyst activity value.